NUTRITIONAL VALUE OF MARANDU PALISADE GRASS ACCORDING TO INCREASING COEXISTENCE PERIODS WITH WEEDS - Belle, J. R.; Marchi, S. R.; Martins, D. [UNESP]; Sousa, A. C.; Pinheiro, G. H. R. (Univ Federal Vicosa, 2018)
This research aimed at evaluating the effect of increasing coexistence periods with weeds on the nutritional components of the forage grass Brachiaria brizantha cv. Marandu under pasture renewal conditions. The experiment was arranged in randomized blocks with four replications, and treatments were represented by eight coexistence periods, namely: 0, 15, 30, 45, 60, 75, 90 and 120 days after seedling emergence. A phytosociologic evaluation was performed on the weed community at the end of the coexistence periods; later, weeds were eliminated by an herbicide formulated with aminopyralid+2,4-D (40+320 g L-1) at 2.5 L ha(-1), applied in post-emergence. The fodder plants were evaluated at the end of the experimental period as for leaf-stem ratio, volumetric density of green leaf, volumetric density of total city matter and main nutritional components, including: crude protein, neutral detergent fiber, ether extract, organic matter and mineral matter, and from this, the total carbohydrate content was calculated. The presence of weeds altered the pasture structure, since it affected negatively the leaf/stem ratio and the volumetric leaf density of B. brizantha. The coexistence also reduced the nutritional components of B. brizantha and determined that control measures should be adopted before reaching 30 days of coexistence between fodder plants and weeds.
Keywords: Brachiaria brizantha; leaf/stem ratio; volumetric density; bromatology; renewal; weed competition